The Effect of Discipline and Workload on Employee Performance with Motivation Mediation on Administrative Bureau Employees Leading of the Regional Secretariat of South Kalimantan Province - Widarto; Irawanto; Riky Welli Saputra; Risda Hayaty (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study entitled The Effect of Discipline and Workload on Employee Performance with Mediation of Motivation on Employees of the Administrative Bureau of the Regional Secretariat of South Kalimantan Province aims to determine the description of discipline, workload, motivation, and performance and to examine the effect of discipline and workload on employee performance mediated with employee motivation. This study uses a quantitative research sample of as many as 30 respondents—data collection using questionnaires and documentation. In comparison, data analysis uses path analysis assisted by SmartPLS 3 software. The results of this study indicate that the work discipline variable (X1) has no effect on employee performance, workload variable (X2) affects employee performance (Y), work discipline variable (X1) does not affect motivation (Z), workload (X2 ) affect work motivation (Z), work motivation (Z) affect employee performance (Y), work discipline (X1) does not affect performance (Y) with the mediation of work motivation (Z), workload (X2) affects performance ( Y ) with work motivation mediation (Z).